(untitled) (Research, Society and Development, 2020)
Maintenance is considered a critical factor in the most diverse fields and is associated with several techniques. Among the existing preventive techniques, the lubrication plan guarantees a good operability of the components. The present study was carried out in a soy processing agribusiness located in the Southwest of the State of Goiás, Brazil, in which a device lubrication plan was identified and proposed. In addition, a survey was prepared between the number of grease applications, the amount of applied grease (g) and temperature (°C) of the components (bearings), and a multivariate regression model was suggested. The study was carried out from the monitoring of the work routines of the maintenance sector in a soy storage line, with the aid of a FLIR thermographic camera model E8. The proposal implemented in the study was able to reduce the costs of man-hours and consumables, and improve the reliability of equipment by the temperature indicator (°C).